OncoDB.HCC: an integrated oncogenomic database of hepatocellular carcinoma revealed aberrant cancer target genes and loci - Su, Wen-Hui (Oxford University Press, 2007)
The OncoDB.HCC () is based on physical maps of rodent and human genomes containing quantitative trait loci of rodent HCC models and various human HCC somatic aberrations including chromosomal data from loss of heterozygosity and comparative genome hybridization analyses, altered expression of genes from microarray and proteomic studies, and finally experimental data of published HCC genes. Comprehensive integration of HCC genomic aberration data avoids potential pitfalls of data inconsistency from single genomic approach and provides lines of evidence to reveal somatic aberrations from levels of DNA, RNA to protein. Twenty-nine of 30 (96.7%) novel HCC genes with significant altered expressions in compared between tumor and adjacent normal tissues were validated by RT–PCR in 45 pairs of HCC tissues and by matching expression profiles in 57 HCC patients of re-analyzed Stanford HCC microarray data. Comparative mapping of HCC loci in between human aberrant chromosomal regions and QTLs of rodent HCC models revealed 12 syntenic HCC regions with 2 loci effectively narrowed down to 2 Mb. Together, OncoDB.HCC graphically presents comprehensive HCC data integration, reveals important HCC genes and loci for positional cloning and functional studies, and discloses potential molecular targets for improving HCC diagnosis and therapy.